A molecular breadboard: Removal and replacement of subunits in a hepatitis B virus capsid. (16th September 2017) - Lee, Lye Siang; Brunk, Nicholas; Haywood, Daniel G.; Keifer, David; Pierson, Elizabeth; Kondylis, Panagiotis; Wang, Joseph Che‐Yen; Jacobson, Stephen C.; Jarrold, Martin F.; Zlotnick, Adam
Abstract: Hepatitis B virus (HBV) core protein is a model system for studying assembly and disassembly of icosahedral structures. Controlling disassembly will allow re‐engineering the 120 subunit HBV capsid, making it a molecular breadboard. We examined removal of subunits from partially crosslinked capsids to form stable incomplete particles. To characterize incomplete capsids, we used two single molecule techniques, resistive‐pulse sensing and charge detection mass spectrometry. We expected to find a binomial distribution of capsid fragments. Instead, we found a preponderance of 3 MDa complexes (90 subunits) and no fragments smaller than 3 MDa. We also found 90‐mers in the disassembly of uncrosslinked HBV capsids. 90‐mers seem to be a common pause point in disassembly reactions. Partly explaining this result, graph theory simulations have showed a threshold for capsid stability between 80 and 90 subunits. To test a molecular breadboard concept, we showed that missing subunits could be refilled resulting in chimeric, 120 subunit particles. This result may be a means of assembling unique capsids with functional decorations.